Cytokines and chemokines multiplex analysis in patients with low disease activity rheumatoid arthritis - Skrzypkowska, Maria; Stasiak, Mariusz; Sakowska, Justyna; Chmiel, Joanna; Maciejewska, Agata; Buciński, Adam; Słomiński, Bartosz; Trzonkowski, Piotr; Łuczkiewicz, Piotr (Rheumatology international, 2022)
Rheumatoid arthritis is a severe chronic autoimmune disorder that results from pathological activation of immune cells and altered cytokine/chemokine network. The aim of our study was to evaluate concentrations of chosen cytokines and chemokines in blood sera and synovial fluid samples isolated from low disease activity rheumatoid arthritis (RA) patients and osteoarthritis (OA) sufferers. Blood sera and synovial fluid samples have been obtained from 24 OA and 14 RA patients. Cytokines/chemokines levels have been determined using a Milliplex ® Map 38-plex human cytokine/chemokine magnetic bead-based panel (Merck Millipore, Germany) and Luminex ® MAGPIX ® platform (Luminex USA). Low disease activity RA patients showed altered concentration of numerous cytokine/chemokine when compared to OA controls—they were characterized by, inter alia, increased: eotaxin/CCL11 ( p = 0.037), GRO/CXCL1 ( p = 0.037), IL-2 ( p = 0.013), IL-4 ( p = 0.017), IL-7 ( p = 0.003), IL-8 ( p = 0.0007) and GM-CSF ( p = 0.037) serum levels, whilst MDC/CCL22 concentration was decreased in this group ( p = 0.034). Eotaxin/CCL11 ( p = 0.001), GRO/CXCL1 ( p = 0.041), IL-10 ( p = 0.003), GM-CSF ( p = 0.01), IL-1RA ( p = 0.0005) and VEGF ( p = 0.01) concentrations in synovial fluid of RA females were also increased. Even with low disease activity score, RA patients exhibited increased concentrations of cytokines with pro- and anti-inflammatory activities, as well as numerous chemokines, growth factors and regulators of angiogenesis. Surprisingly, RA subjects also shown decreased concentration of CCL22 chemokine. The attempt to restore cytokine balance and tolerogenic environment is ineffective in RA sufferers even with good disease management. Distinguished factors could serve as possible indicators of disease progression even in low disease activity patients.